HUBUNGAN SUPERVISI, REKAN KERJA, GAJI, KEAMANAN KERJA, KONDISI KERJA, PROMOSI JABATAN DAN JENIS PEKERJAAN DENGAN KEPUASAN KERJA (Studi Kasus Pada Karyawan Koperasi Simpan Pinjam X di Kabupaten Pemalang, Jawa Tengah) - Kurnia Dwi Yuda Putra; Ida Wahyuni; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Job satisfaction is the attitude of the worker to the work he does. Job satisfaction must be considered by human resource managers because it isrelated to level of health, performance, sustainability of labor (persistence) and productivity. The purpose of this study is to analyze the correlation between supervision, co-workers, salary, job security, work conditions, promotion and type of work with job satisfaction of employees of Union Savings and Loans X. This research is analytical research using cross-sectional study which is a form of observational research design. The population and sample in this research are 34 employees of Union Savings and Loans X. The instrument that used in this research are Minnesota Satisfaction Questionnaire (to measure job satisfaction), Job Description Indexquestionnaire (to measure supervision, co-workers, salary, promotion and job type) and also job security and working conditions questionnaire. The result showed that there is correlation between supervision (sig = 0,034), salary (sig = 0,000), job security (sig 0,034), work condition (sig = 0,012), promotion (sig = 0,40) with job satisfaction. There is no correlation between co-workers (sig = 1,000) and job type (sig = 0.225) with job satisfaction. As many as 50% of employees are satisfied with their work. To increase employee satisfaction, the company should improve supersvision system, provide a fair payment system, improve the company security system, complete the jobsupport facility and improve the position promotion rule.